Publisher's note - Papageorgiou, Konstantinos (Epistēmēs Metron Logos, 2020)
The current issue of EML comes with three important changes. First and foremost, we have a new Editor in Chief: Professor Panagiotis Vlamos, the head of the Informatics Department of the Ionian University, a distinguished academic and mathematician. The second important change is the official opening of the EML’s webpage within the National Documentation Center’s platform. This means that all editorial and publishing workload will be processed automatically via the publishing platform of the NDC providing increased functionality for both writers and editors. The third important change is language. In an effort to make EML a truly international journal, apart from the obvious and necessary first step to staff the editorial board highly esteemed academics from around the globe, which we have accomplished, we have decided to publish articles in the English language only. This decision will be in effect starting on the July 2020 issue. I want to thank all sides, writers, editors, NDC, for your contribution in making EML a top of the line journal and I wish to commit to continuous innovative and evolving future editions!